Ensuring the Safety of Sunscreens, and Their Efficacy in Preventing Skin Cancers: Challenges and Controversies for Clinicians, Formulators, and Regulators - Paul, Sharad P. (Frontiers in Medicine, 2019)
When people think about sun-protection or prevention of skin cancer, sunscreens readily come to mind. Sunscreen effectiveness is tested in vivo by the ability to prevent erythema of skin, yet testing methods vary between markets, and many sunscreens fail to achieve their claims. This article discusses the mechanism of action of sunscreens, Sun Protection Factor (SPF), safety concerns and the challenges for regulators. Many sunscreens that prevent erythema do not provide adequate protection as they contain anti-inflammatory agents; others have ingredients whose risks have not been fully evaluated. This article reviews the imperfect science behind sunscreens and points out the gaps in knowledge regarding safety, efficacy, public knowledge and perception. Regulations vary between countries and only adds to the confusion. To truly prevent skin cancer, clinicians, formulators and regulators need to come together to research more and improve public education.